Reporting bad news on software projects: the effects of culturally constituted views of face-saving - Keil, Mark; Im, Ghi Paul; Mähring, Magnus (Information systems journal (Oxford, England), 2007)
.  The reluctance to report bad news about a project and its status is a known problem in software project management that can contribute to project failure. The reluctance to report bad news is heightened when it bears personal risks. Oftentimes, those who report bad news end up losing face. In extreme cases, they not only lose face, but may end up on the unemployment line. The need to preserve face is a powerful influence on social behaviour. While universal, it manifests itself differently in different cultures. To date, there have been no empirical studies of the extent to which culturally constituted views of face‐saving affect reporting of bad news on software projects. This is a particularly important topic given the increased prevalence of global, dispersed software development teams and offshore outsourcing of software development. In this study, we conducted a role‐playing experiment in the USA and in South Korea, to investigate the effect of culturally constituted views of face‐saving on the willingness to report bad news regarding a software development project. A blame‐shifting opportunity was chosen as the means to operationalize face‐saving in a culturally sensitive fashion. The two countries were chosen because they differ markedly in their views of face‐saving and the relative importance ascribed to two important aspects of face: lian and mianzi. Results reveal that the presence of a blame‐shifting opportunity had a significant effect on US subjects’ willingness to report bad news, but the effect on Korean subjects was not found to be statistically significant. In the absence of a blame‐shifting opportunity, we did not observe any significant differences between US and Korean subjects in willingness to report bad news. The implications of these findings are discussed.